Rekonstruksi Metodologi Pengembangan Sains Berbasis Agama - Muslih, Mohammad (KALAM, 2017)
The development of an integrative scientific paradigm is certainly a very large scientific project, however, it must be admitted that the success of reconstructing the new paradigm is still insufficient, as it must be supported by the availability of a functional and effective methodology. This article is a study aimed at offering a methodology for integrative paradigm-based science development, which is not only functional and effective, but also ensures productivity, as well as secure from the pseudo-scientific of abusive practices and the excessive practice of ideological science. The reconstruction of a methodology of religious-based science development urged to do, on the one hand, to provide an answer to the doubt about its compatibility with the Islamic sciences, and on the other hand deny the fear of the disappearance of Islamic values, precisely with the continued execution of scientific research, or the development of scientific reason, in general.Pembangunan paradigma ilmiah integratif sudah tentu merupakan proyek keilmuan yang sangat besar, meski demikian, harus diakui, keberhasilan melakukan rekonstruksi paradigma baru itu masih belum cukup, sebab masih harus didukung oleh tersedianya metodologi yang fungsional dan efektif. Artikel ini merupakan kajian bermaksud menawarkan metodologi pengembangan sains berbasis paradigma integratif, yang tidak hanya fungsional dan efektif, tetapi juga menjamin produktivitas, sekaligus aman dari jeratan praktek kasar pseudosaintifik dan praktek berlebihan sains ideologis. Rekonstruksi metodologi pengembangan ilmu berbasis agama mendesak untuk dilakukan, di satu sisi untuk memberi jawaban atas keraguan akan kompetabilitasnya dengan ilmu-ilmu keislaman, dan pada sisi yang lain membantah kekhawatiran akan hilangnya atau terkikisnya nilai-nilai keislaman, justru dengan semakin dijalankannya riset-riset ilmiah, atau dikembangkannya nalar ilmiah secara umum